WOMEN AND SOCIAL JUSTICE: AN ECONOMIC ANALYSIS OF EXCLUSION AND INEQUALITY (International Journal of Food and Nutritional Sciences, 2022)
In India, women in general and poor rural women in particular, are comparatively powerless in the economic and political sphere of life. In developing countries women hold 8 per cent of the administrative and managerial positions whereas in developed countries it has raised up to 24 per cent. They face lot of problems since childhoods till old age. More than 15 million girls are born every year in India. According to the survey report of UNICEF’s million girls died in India. Gender discrimination is also one of the main causes of death. Child marriage is considered as protection against sexual molestation. Child marriage is considered as protection against sexual molestation. Crimes against women as molestation, rape, prostitution, cruelty by husband and other members and dowry death have reached an alarm level everywhere. This is due to the growth of population copied with involvement of outside criminals, loosing of social control, increased violence in social interaction as well as political activities. The traditional concept of justice has been replaced by the modern concept of social justice. Social justice is associated with social equality and social rights. It aims at removing exploitation, oppression and discrimination in society. This present paper aims at discussing the status of women and they are excluding from social justice in India.